Agent-Based Modeling as a Legal Theory Tool - Benthall, Sebastian; Strandburg, Katherine J. (Frontiers in Physics, 2021)
Agent based modeling (ABM) is a versatile social scientific research tool that adapts insights from physics to study complex social systems. We argue that ABMs should be used more often in the fields of legal theory and legal design. The highly influential approach of Law and Economics (L&E) has shown how a quantitative discipline can have significant and long-lasting impact on the shape of the law. But while L&E has generated powerful and actionable insights for law, its analytic simplicity has biased its normative implications. We point to three recent critiques of L&E: from macroeconomics, from law and political economy (LPE), and from complex systems research. ABM methods can address these critiques and make an impact on legal theory and design, but only if the temptation to make them too intricate is avoided and the models can deliver general and easy-to-understand results.